Tiotropium for the Treatment of Asthma: Patient Selection and Perspectives - V. Madhu Chari; Robert Andrew McIvor (Canadian Respiratory Journal)
Asthma is a chronic disease of airway inflammation with a large global burden. Despite established, guideline-based stepwise therapy, a significant proportion of patients remain symptomatic and poorly controlled. As such, there is a need for additional safe, effective, convenient, and cost-effective therapies that can be broadly applied across a range of asthma phenotypes. Tiotropium is a long-acting muscarinic antagonist (LAMA) that leads to bronchodilation by blocking endogenous acetylcholine receptors in the airways. Tiotropium has long been approved for the treatment of chronic obstructive pulmonary disease, and it has recently been recognized for its safety and efficacy in improving lung function and controlling asthma. Evidence from several Phase III trials in the adult and paediatric population has shown that tiotropium is well tolerated and significantly improves a range of endpoints as an add-on treatment to ICS therapy, regardless of baseline characteristics and clinical phenotypes. Consequently, regulatory authorities worldwide have recently licensed tiotropium as the only LAMA approved for the treatment of asthma. This review provides an overview of safety and efficacy data and discusses the use of tiotropium in patients across the range of asthma severities, ages, and phenotypes.